ANALISA PENGEMBANGAN KAPASITAS LAHAN PARKIR PASAR AEK GODANG KEC. HULU SIHAPAS KAB. PADANG LAWAS UTARA - Uddin Hasibuan; Ahmad Rafii; Afniria Pakpahan (STATIKA, 2026)
Parking is a stationary state of a vehicle that is temporary in nature because it is left by the driver at certain places, whether indicated by traffic signs or not, and is not solely for the purpose of boarding and/or alighting passengers and/or loading goods. Parking facilities are an inseparable element of the overall highway transportation system. Many vehicles park on the roadway, which is caused by the available parking capacity being unable to accommodate the volume of vehicles, particularly regarding parking facilities. This study aims to determine the volume, duration, capacity, and development of parking spaces for two-wheeled and four-wheeled vehicles at Aek Godang Market. From the research results, it was found that the parking volume for motorcycles was 321 units and for cars was 60 units, with an average parking duration of 1 hour 28 minutes per vehicle for motorcycles and 135 minutes per vehicle for cars. The parking turnover rate for motorcycles was higher compared to cars. The existing parking capacity at Aek Godang Market for motorcycles is 162 SRP (Parking Space Units), while the parking demand is 250 SRP. Meanwhile, the existing car parking capacity is 30 SRP, while the demand is 54 SRP. Based on the parking volume at Aek Godang Market, it indicates that the parking space requirements for motorcycles and passenger cars cannot be met by the existing capacity. To add 88 SRP of parking spaces for motorcycles, a land area of 355 m² is required, while passenger cars urgently need an additional land area of approximately 180 m². The available potential land for parking development is located in front of the Aek Godang Market shophouses, which offers sufficient area. Keywords: volume, capacity, duration, development